Analyzing Vocabulary Learning through the Lens of Students' Learning Styles: A Framework for Arabic Language Teaching - Amilya,; Yul, Widiya (Shaut al Arabiyyah, 2025)
The objective of this research is to determine the alignment of teaching techniques applied at SMP Atthayyibah in vocabulary instruction with the individual learning styles of students. The method used in this research is qualitative. The findings reveal that teachers have not engaged in mapping the students' learning styles in the context of Arabic language instruction. However, it is noteworthy that teachers implement vocabulary teaching strategies that cater to different learning styles, encompassing auditory, visual, and kinesthetic learners. These strategies include 1) utilizing visual aids, 2) implementing singing techniques, and 3) conducting lessons outside the classroom. The primary challenge encountered by teachers in mapping students' learning styles is the difficulty in determining subsequent actions once the mapping is completed. The findings of this study suggest that teachers who do not map students' learning styles tend to avoid making additional efforts to prepare strategies tailored to the identified learning styles.